2014
DOI: 10.1002/bsl.2138
|View full text |Cite
|
Sign up to set email alerts
|

What Factors Are Related to Success on Conditional Release/Discharge? Findings from the New Orleans Forensic Aftercare Clinic: 2002‐2013

Abstract: The present study investigated the empirically based factors that predicted success on conditional release among a sample of individuals conditionally discharged in Louisiana. Not guilty by reason of insanity acquittees and individuals on conditional release/discharge for incompetency to stand trial were included in the study. Success on conditional release was defined as maintenance of conditional release during the study period. Recidivism (arrest on new charges) and incidents were empirically evaluated. Suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Literature demonstrates that revocations for rule violations are higher than revocations for acquisition of new criminal charges (Vitacco, Vauter, Erickson, & Ragatz, 2014;Wiederanders, 1992). Revocation rates of rule violations range from 5% to 49% (Bertman-Pate et al, 2004;Callahan & Silver, 1998;Green et al, 2014;Manguno-Mire, Coffman, DeLand, Thompson, & Myers, 2014;Vitacco et al, 2008;Vitacco et al, 2014;Wiederanders, Bromley, & Choate, 1997) over different follow-up periods ranging from 1.7 to 5.1 years.…”
Section: Medium Security Treatment and Recidivism Ratesmentioning
confidence: 97%
“…Literature demonstrates that revocations for rule violations are higher than revocations for acquisition of new criminal charges (Vitacco, Vauter, Erickson, & Ragatz, 2014;Wiederanders, 1992). Revocation rates of rule violations range from 5% to 49% (Bertman-Pate et al, 2004;Callahan & Silver, 1998;Green et al, 2014;Manguno-Mire, Coffman, DeLand, Thompson, & Myers, 2014;Vitacco et al, 2008;Vitacco et al, 2014;Wiederanders, Bromley, & Choate, 1997) over different follow-up periods ranging from 1.7 to 5.1 years.…”
Section: Medium Security Treatment and Recidivism Ratesmentioning
confidence: 97%
“…The HOM meso-measurements can provide for this much needed evidence based working model to research empirically validated factors to augment our empirical understanding of CR patients as to enhance CR risk assessment and management programmes. Moreover, in line with recommendations of Manguno-Mire et al (2014) and Marshall et al (2014), the HOM model provides for the comparable patient release groups (without follow-up), that are needed to further research the effectiveness of CR. Hence, the HOM meso-measurements provide for the empirical data to enhance and validate treatment effectiveness of CR programmes, to ultimately augment the public safety.…”
Section: Meso-levelmentioning
confidence: 82%
“…For example, it was shown that the historical HCR-20 scale , living arrangement (Marshall et al, 2014;Novosad et al, 2014), financial resources, personality disorder, substance use disorder and number of incidents in the CR programme, were related to revocation of CR (Manguno-Mire et al, 2014). As highlighted by several scholars (Crocker et al, 2014;Gowensmith et al, 2014;Green et al, 2014;Manguno-Mire et al, 2014), more research into empirically validated CR related risk and protective factors is needed to provide the clinical and legal practice with an empirical basis to standardize the decision-making process into CR and to develop successful CR programmes. The HOM meso-measurements can provide for this much needed evidence based working model to research empirically validated factors to augment our empirical understanding of CR patients as to enhance CR risk assessment and management programmes.…”
Section: Meso-levelmentioning
confidence: 98%
See 1 more Smart Citation
“…It serves individuals on conditional release, including those who are on supervised probation and those who have not yet been adjudicated. Detailed information about the New Orleans FAC and defendants on conditional release has been previously described by Manguno‐Mire et al (). The FAC is the only free‐standing outpatient forensic clinic in the state of Louisiana and is located 114 miles from the maximum security forensic hospital in rural northern Louisiana.…”
Section: Description Of Outpatient Competency Restoration Treatment Smentioning
confidence: 99%